STUDY OF THE INDONESIAN MARITIME SECURITY INDEX - Habibie Masherudin, M.
Indonesia has abundant natural resources in its seas, such as fish and mineral resources on the seabed. The waters and oceans of Indonesia play a crucial role in the social and economic life of the Indonesian people. Tourism, fisheries, maritime trade, ocean exploration and exploitation, and maritime transportation are vital sectors for the country. To fully capitalize on this potential, Indonesian waters must be secure, free from threats, and protected. Currently, there is an indicator to describe the level of security in Indonesian waters, known as the Maritime Security Index, officially established by the Indonesian Maritime Security Agency (Bakamla RI). The concept of the blue economy combines economic development with environmental conservation. Maritime security and the blue economy share the common goal of protecting the ocean but employ different approaches. Maritime security safeguards the ocean by eliminating threats, while the blue economy protects the ocean by utilizing it sustainably. Therefore, the Blue Economy can serve as an indicator to measure the level of security in Indonesian waters and Indonesia's jurisdictional waters. Based on this idea, the question arises: how can the blue economy be applied in the Maritime Security Index? The methodology used is literature study, data collection, conceptualization and analysis. There are three sectors of maritime economic development that constitute sub-dimensions of the Blue Economy in the Maritime Security Index: the fisheries sector, maritime industry sector, and maritime tourism sector. These three sectors can be considered as parameters for the Maritime Security Index.